2013
DOI: 10.15580/gjpbcs.2013.1.031913533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time and Rate of Application of Bateleur Gold (S-Metolachlor + Flumetsulam) on Phytotoxicity and Weed Control Efficacy in Flue-cured Tobacco

Abstract: Herbicides are usually the first line of defence against weeds and form a formidable pair with mechanical control whether with machinery of hand hoeing. Due to the risk of weed resistance to herbicide control and environmental contamination, there is continuous need for new chemicals to be tested for control of weeds. In this work, the herbicide Bateleur Gold, a factory premix of s-metolachlor and flumetsulam was evaluated to establish the time and rate of application that would give efficacious weed control w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…This proved that herbicides are effective in reducing the weed spectrum in maize fields. This is in agreement with results by Mazarura (2013) who reported that flumetsulam (triazolopyrimidine sulfonanilide) + S-metolachlor (chloro-acetanilide) was effective in controlling weeds on flue cured tobacco. On the second assessment done 14 days after the application of the pre-emergence herbicide, the flumetsulam (triazolopyrimidine sulfonanilide) + S-metolachlor (chloro-acetanilide) treatment scored a 98% on the EWRC scale in terms of weed density and Smetolachlor treatment scored 90%.…”
Section: Flumetsulamsupporting
confidence: 93%
See 1 more Smart Citation
“…This proved that herbicides are effective in reducing the weed spectrum in maize fields. This is in agreement with results by Mazarura (2013) who reported that flumetsulam (triazolopyrimidine sulfonanilide) + S-metolachlor (chloro-acetanilide) was effective in controlling weeds on flue cured tobacco. On the second assessment done 14 days after the application of the pre-emergence herbicide, the flumetsulam (triazolopyrimidine sulfonanilide) + S-metolachlor (chloro-acetanilide) treatment scored a 98% on the EWRC scale in terms of weed density and Smetolachlor treatment scored 90%.…”
Section: Flumetsulamsupporting
confidence: 93%
“…Flumetsulam (triazolopyrimidine sulfonanilide inhibit acetolactate synthase which catalyses biosynthesis of amino acids. It has been used in controlling weeds in tobacco and has proven to be effective (Mazarura, 2013). Therefore the objectives were to assess the efficacy of S-metolachlor and flumetsulam (triazolopyrimidine sulfonanilide)+Smetolachlor (chloro-acetanilide) pre-emergence herbicides in maize production.…”
Section: Introductionmentioning
confidence: 99%